2010
DOI: 10.1002/adma.200901327
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functionalities of Polyelectrolyte Multilayer Films: New Biomedical Applications

Abstract: The design of advanced functional materials with nanometer- and micrometer-scale control over their properties is of considerable interest for both fundamental and applied studies because of the many potential applications for these materials in the fields of biomedical materials, tissue engineering, and regenerative medicine. The layer-by-layer deposition technique introduced in the early 1990s by Decher, Moehwald, and Lvov is a versatile technique, which has attracted an increasing number of researchers in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
702
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(720 citation statements)
references
References 306 publications
(322 reference statements)
3
702
0
7
Order By: Relevance
“…Nowadays these multilayer films are extensively used as reservoirs to host bioactive molecules aiming at biological applications. [6][7][8][9][10] A variety of molecules can be embedded into the films; they include small drugs and dyes, [11][12][13][14][15][16][17] proteins and peptides, [18][19][20][21] or nucleic acids. 22,23 Extensive reviews on the reservoir properties of the multilayers can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays these multilayer films are extensively used as reservoirs to host bioactive molecules aiming at biological applications. [6][7][8][9][10] A variety of molecules can be embedded into the films; they include small drugs and dyes, [11][12][13][14][15][16][17] proteins and peptides, [18][19][20][21] or nucleic acids. 22,23 Extensive reviews on the reservoir properties of the multilayers can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Extensive reviews on the reservoir properties of the multilayers can be found elsewhere. 6,7,10,24 Multilayers assembled from the biopolymers hyaluronic acid (HA) and poly-L-lysine (PLL) are some of the most studied systems. The HA/PLL multilayers are non-toxic for a variety of cell lines and have been employed to control cell adhesion via chemical or physical cues.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes can be encapsulated in such films and remain active for longer time durations than in solution [78]. Many bioapplications of PEM films are reported and have been reviewed [79,80]. Of particular interest is the finding that a change in the mechanical properties allows to fine tune not only the cellular adhesion [81], but also the level of nuclear expression of the adherent cells [82].…”
Section: Selected Applications Of Films Produced In a Sbs Mannermentioning
confidence: 99%
“…In simple terms, the proposed solution provided the structural support to the cells. The ECM-like structure play an important role in modulating numerous cellular functions including: cell adhesion, migration, proliferation and differentiation [20][21][22][23]. For this reason, the use of synthetic materials, like polyelectrolyte was proposed.…”
Section: An Important Aspect In the Development Of An Effective Treatmentioning
confidence: 99%